Feasibility and Safety of Paclitaxel-Coated Balloon Angioplasty for the Treatment of Intracranial Symptomatic In-Stent Restenosis - Xu, Haowen; Fu, Xiaojie; Yuan, Yongjie; Quan, Tao; Wang, Zibo; Han, Kaihao; Liu, Guo; Guan, Sheng (Frontiers in Neurology, 2020)
Objective: Symptomatic in-stent restenosis (sISR) is the major cause of medium- or long-term cerebral infarctions in patients who underwent percutaneous transluminal angioplasty and stenting (PTAS) for severe intracranial atherosclerotic stenosis (ICAS). This study aims to evaluate the feasibility and safety of paclitaxel-coated balloon (PCB) angioplasty for the treatment of intracranial sISR. Methods: We report 11 cases of PCB angioplasty for intracranial sISR. Lesion locations and number were as follows: intracranial internal carotid artery (n=4), M1 segment of middle cerebral artery (MCA) (n=1), V4 segment of vertebral artery (n=6). The technical success rate, periprocedural complications and short-term outcome were retrospectively analyzed. Results: All procedures were successfully performed without periprocedural complication. Asymptomatic vessel dissection after PCB inflation occurred in one case. Postprocedural DWI showed new asymptomatic ipsilateral infarction in one case. All 11 cases did not experience ipsilateral stroke or death within 30 days or ischemic stroke in the territory of the target artery between 31 and 90 days after procedure. Conclusion: This preliminary study indicates that PCB angioplasty is feasible and safe for the treatment of intracranial sISR. Further studies are needed to clarify its efficiency and long-term outcome.